2018
DOI: 10.7554/elife.32679
|View full text |Cite
|
Sign up to set email alerts
|

CK1/Doubletime activity delays transcription activation in the circadian clock

Abstract: In the Drosophila circadian clock, Period (PER) and Timeless (TIM) proteins inhibit Clock-mediated transcription of per and tim genes until PER is degraded by Doubletime/CK1 (DBT)-mediated phosphorylation, establishing a negative feedback loop. Multiple regulatory delays within this feedback loop ensure ~24 hr periodicity. Of these delays, the mechanisms that regulate delayed PER degradation (and Clock reactivation) remain unclear. Here we show that phosphorylation of certain DBT target sites within a central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…While these studies were elegantly done using available tools, overexpression studies carry the potential problem of gain of function. Moreover, proteins that regulate the core molecular clock have significantly different roles in different clock neurons (Top et al, 2016; Top et al, 2018). The best genetic tools are those that cause loss of function.…”
Section: Discussionmentioning
confidence: 99%
“…While these studies were elegantly done using available tools, overexpression studies carry the potential problem of gain of function. Moreover, proteins that regulate the core molecular clock have significantly different roles in different clock neurons (Top et al, 2016; Top et al, 2018). The best genetic tools are those that cause loss of function.…”
Section: Discussionmentioning
confidence: 99%
“…While these studies were elegantly done using available tools, overexpression studies carry the potential problem of gain of function. Moreover, proteins that regulate the core molecular clock have significantly different roles in different clock neurons (55,56). The best genetic tools are those that cause loss of function.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, tim(S1404D) flies also exhibited shortened period, similar to what was observed in tim(S1404A) flies (Figures 1B and S1B; Table S2). Although it is logical to assume that nonphosphorylatable and phosphomimetic mutations should result in opposite phenotypes (e.g., Top et al 31 and Chiu et al 41 ), that is often not the case, as observed in previous phosphorylation studies (e.g., Lin et al, 28 Chiu et al, 42 and Top et al 45 ). Furthermore, although both tim(S1404A) and tim(S1404D) mutants exhibit period shortening at the behavioral level, the underlying molecular mechanisms that underlie their phenotypes may differ.…”
Section: Transgenic Flies Expressing Non-phosphorylatable Tim Variantmentioning
confidence: 97%
“…35 Significant progress has been made in examining the function of site-specific PER phosphorylation, enabling in-depth mechanistic understanding of post-translational regulation of PER subcellular localization, repressor activity, and degradation to generate a 24-h rhythm. 28,29,[41][42][43][44][45] On the other hand, the relative dearth of studies that characterize site-specific functions of TIM phosphorylation 22,31,46 remains a significant obstacle to fully understand the regulation of circadian rhythms via post-translational regulation of TIM and PER-TIM complexes. In this study, we used mass spectrometry proteomics to identify phosphorylation sites of PER-bound TIM proteins purified from Drosophila heads.…”
Section: Introductionmentioning
confidence: 99%